2018
DOI: 10.1002/pola.29053
|View full text |Cite
|
Sign up to set email alerts
|

Design, synthesis, and gas permeation properties of polyimides containing pendent imidazolium groups

Abstract: Film‐forming polymers containing ionic groups have attracted considerable attention as emerging materials for gas separation applications. The aim of this article was to synthesize new film‐forming polyimides containing imidazolium groups (PI‐IMs) and establish their structure–performance relationship. In this context, a new aromatic diamine, namely, N1‐(4‐aminophenyl)‐N1‐(4‐(2‐phenyl‐1H‐imidazol‐1‐yl)phenyl)benzene‐1,4‐diamine (ImTPADA), was synthesized and polycondensed with three aromatic dianhydrides, name… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 42 publications
1
2
0
Order By: Relevance
“…65 Although 6FDA-BASA show relatively large gas permeability, the selectivity is reduced. But it can be observed that compared with PI-6FDA 66 with similar gas permeability reported at present, the gas selectivity of 6FDA-BASA has no great loss. The O 2 permeability and O 2 /N 2 selectivity of 6FDA-BASA were closest to the 1991 upper bound.…”
Section: Resultssupporting
confidence: 79%
“…65 Although 6FDA-BASA show relatively large gas permeability, the selectivity is reduced. But it can be observed that compared with PI-6FDA 66 with similar gas permeability reported at present, the gas selectivity of 6FDA-BASA has no great loss. The O 2 permeability and O 2 /N 2 selectivity of 6FDA-BASA were closest to the 1991 upper bound.…”
Section: Resultssupporting
confidence: 79%
“…For the sPI prepared via solvothermal polymerization, the PXRD pattern shows a broad peak indicating its amorphous feature. 19 While cPI prepared via conventional polymerization displays a weak peak at 5.691 corresponding to the (200) plane, suggesting a low crystallinity with poor long-range periodicity. 20 It is noteworthy to mention that PI-COF reveals the first and most intensive peak at 2.71 attributed to (100) along with minor peaks at 5.61 and 7.31 assigned to the (200) and (210) planes, respectively, demonstrating the formation of ordered domains with high crystallinity (as illustrated in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…29,30 In previous work, some aromatic PIs and poly(ether imide)s containing di-and triarylimidazolyl units into the polymer backbone or as bulky pendant groups have been reported. [31][32][33][34][35][36][37][38][39] In this paper, with an aim to develop high performance and processable PIs, a new kind of unsymmetrical diamine containing tetraarylimidazolyl and trifluoromethyl groups, 1,2diphenyl-4,5-bis(4-trifluoromethylphenyl)-1H-imidazole, has been synthesized successfully. Meanwhile, a new series of fluorinated imidazolyl-containing PIs were synthesized derived from the resulting diamine monomer.…”
Section: Introductionmentioning
confidence: 99%